Effects of ambient temperature and available sugar on bacterial community of Pennisetum sinese leaf: An in vitro study - Lu, Guangrou; Huang, Xiaokang; Li, Lin; Chen, Chao; Li, Ping (Frontiers in Microbiology, 2023)
The present in vitro study investigated the effects of temperature and available sugar on the bacterial community of Pennisetum sinese leaf during fermentation. P. sinese leaves were cultured in MRS broth containing 0.4 and 1.6 g sugar and incubated at 25°C and 45°C for 9, 18, and 36 h. The results showed that the dominant phyla during sugar fermentation were Firmicutes, followed by Proteobacteria and Bacteroidetes. Compared to a low incubation temperature (25°C), a high incubation temperature (45°C) decreased the relative abundances of Exiguobacterium and Acinetobacter and increased those of Bacillus and Paenibacillus. Leaf samples incubated at 25°C showed higher bacterial alpha diversity indices than those incubated at 45°C. Principal coordinate analysis revealed that the bacterial community structure was altered by the high incubation temperature. Sugar concentration of 1.6g/50ml increased the relative abundances of Bacillus and Klebsiella but decreased those of Paenibacillus and Serratia as compared to sugar concentration of 0.4g/50ml. pH was the primary factor that influenced the succession of bacterial communities during sugar fermentation in P. sinese leaves. In conclusion, ambient temperatures（25℃ and 45℃）and high sugar concentration restructured the bacterial communities on P. sinese leaves by facilitating the dominance of Bacillus and Paenibacillus. This study provided insights into the mechanisms by which bacterial communities on P. sinese leaves are enriched.